Ultrasound of Postoperative Ankle Instability: How to Manage with Arthroscopic Reparation or Anatomical Reconstruction of Lateral Ankle Ligaments - Dallaudière, Benjamin; Dalmau-Pastor, Miki; Pesquer, Lionel; Boudahmane, Sofiane; Cordier, Guillaume (Seminars in Musculoskeletal Radiology, 2024)
Surgical repair or reconstruction of lateral ankle ligaments is indicated in patients with persistent ankle instability, with arthroscopic/endoscopic treatment becoming more frequent. Although presurgical imaging of the ankle is always standard procedure, more is needed to understand the evolution of the repaired ligament or the tendinous graft to help improve length of postoperative time and functional results. This review describes the normal ultrasound aspects and possible complications of repaired/reconstructed ankle ligaments after an all-inside endoscopic repair/reconstruction of the anterior talofibular ligament and the calcaneofibular ligament.
Keywords: ultrasound; ankle; surgery; ligament; reconstruction